Hyper resolute laser writing mediated by tailored ENZ matematerials: the specifc case of all-dielectric broadband metalenses - Lio, Giuseppe Emanuele; Cipparrone, Gabriella; Caputo, Roberto; Giocondo, Michele; De Luca, Antonio (Università della Calabria, 2021)
Metamaterials are part of an emerging research field with a broad range of useful potential applications in cross-disciplinary fields spanning material science, optics, industrial applications, and last but not least, sensing from environmental hazards to cancer cells. Metamaterials present particular features especially when they are fabricated as multi-stack layered systems or optical nano-cavities. In fact, due to the particular features presented by this kind of materials as strong self-collimation and canalization effects, extraordinary transmittance and plasmonic behavior, they open a very wide scenario of nano-technological applications. The application that has been addressed in this thesis exploits the interesting and intriguing features of metal/ insulator/ metal/insulator systems, so-called MIMIs, in optical nano-cavities configuration tailored to drastically improve the resolution of a generic Two Photon Direct Laser Writing (TP-DLW) lithography process. The enhanced technique covers an important role in nanotechnology and especially in new nanomaterials frontiers for the possible realization of polymeric, thus completely dielectric, metasurfaces. For these reasons, the driving concept of the work presented in this research activity is to carry out the entire cycle of realization of MIMI devices, passing from their design, optimization, fabrication and characterization. Following their realization, the optimized MIMI are used to enhance the TP-DLW process in order to fabricate hyper-resolute test samples as 1D gratings, 2D metasurfaces and 3D complex objects. Given its self-collimation optical features, the MIMI metamaterial is used for the characterization of the realized structures as well. A specific, noticeable case that has been addressed in this thesis is the realization of ultra-flat all-dielectric apochromatic broadband metalenses assisted, during the design, by a Deep Machine Learning algorithm and, for their fabrication, by the above mentioned enhanced TP-DLW process. Finally, the realized metalenses have been optically characterized in the visible spectrum (300 − 1000 nm) confirming (as designed) fascinating features if compared with the already realized metalenses like the numerical aperture, extended focal length and depth of focus. Chapter 1 introduces the main aspects of metamaterials, as well as, the isofrequency surface describing the dispersion relations of hyperbolic metamaterials, and different geometrical configurations that allow exploiting particular physical effects and behaviors in light-matter interaction. Then, stacked multi-layer materials and a particular family of those, #psilon Near Zero, are presented. These metamaterials are a particular class of artificial optical structures consisting of a periodic arrangement of metallic and dielectric layers able to self-collimate and canalize light inside themselves. Finally, the chapter concludes with an overview of the plasmonic behavior in a simple metal/insulator interface that produces surface plasmon polaritons. Then it considers the bulk plasmon polaritons in multi-stacked metamaterials and the gap surface plasmon in Fabry-Perot nano-cavities. In Chapter 2, a simple and fast, yet robust, way to design metamaterials is evaluated as a function of their optical response and behavior. In fact, the first topic addressed in this chapter is ellipsometry and related advantages, to characterize nano-structures by retrieving the ellipsometric parameters Y and D, reflectance and transmittance and the complex refractive index n − ik. Then, the Transfer Matrix Method (TMM) has been detailed and used to code a homebuilt Matlab tool to predict the optical behavior as a function of the metamaterials design. On the same way, by using COMSOL Multiphysics, a Numerical Ellipsometer Analysis (NEA) has been realized. NEA covers the role of a robust tool to predict the optical response in much complex systems such as multi-layered materials with/without superstructures (gratings, holes, helices) placed above them. Some numerical simulations predicted by the NEA are experimentally validated by different cases with increasing system complexity. The plasmonic dispersion relations and the modal analysis have been addressed for dielectric cavities that support multi-spectral modes in the visible. Finally, in the last section, particular effects produced by MIMI cavities have been studied. Two key aspects related to the optical cavities are presented below. The first concerns the way they show hues / shades of color as a function of the cavity thickness and the involved material; the second one is a fast and effective way to identify the plasmons propagating inside these structures through the pseudo-dielectric function < ˜# >. These designed cavities present also particular effects like a large de-phasing well-known as Goos-Hänchen shift, that it is exploitable for extremely accurate sensing. Chapter 3 begins by introducing the main concepts of one and two-photon lithography and describing the state of the art of the Two-Photon Direct Laser Writing (TP-DLW) process. Then, as reported in the previous chapter, it shows detailed aspects of optical-nano cavities and leverages on the MIMI properties and features to design an embedded device able to work at the two photon lithography process wavelength (l = 780nm). The fabricated prototype is tested in terms of the incident beam waist modification by the evaluation of the Point Spread Function (PSF) reduction, measured by an homebuilt confocal setup equipped with a beam profiler. After its characterization, the MIMI device is used to realize 1D gratings compared with the ones fabricated through standard glass substrates. The reduction of 89% in height and 50% in width challenges our research product to reproduce the portrait "The Lady with an Ermine" by Leonardo Da Vinci that exhibits an high resolution level in terms of details and the nanoscale slicing in the 3D fabrication Chapter 4. The results obtained by the enhanced TP-DLW technique are exploited, in this chapter, to realize all-dielectric apochromatic broadband "flatland" metalenses with overall thickness less than 50nm. For their de facto two-dimensional nature, we call them "flatland" metalenses with the obvious reference to the famous Abbott’s novel ("Flatland: A Romance of Many Dimensions"). Next generation optics follow the trendsetting of miniaturized devices with extraordinary features as extended focal length and Depth of Focus (DOF), high Numerical Aperture and, last but not least, fast and easy way to produce them. In fact, this extremely flat design is the result of the novel two-photon direct laser writing (TP-DLW) process enhanced to hyper resolution performance by leveraging on the peculiar optical properties of our designed and developed ENZ metamaterials. Once fabricated, the characterization of the metalenses follows by means of a homebuilt setup equipped with beam-profiler and spectrometer. This measurement provided the characteristic values for these features like focal length f = 1.14mm, DOF in the range |50 − 150|μm and the numerical aperture NA = 0.087. In summary, the improved resolution of TP-DLWprocess presented in Chapter 3 is extremely significant for industrial applications in several fields such as anti-counterfeiting and flat optics, as shown in the last two Chapters of this Thesis work.
Dottorato di ricerca in Scienze e tecnologie fisiche, chimiche e dei materiali. Ciclo XXXIII
Keywords: Matematerials; ENZ; Optical nano-cavity; Direct laser writing; Hyper resolution